À la recherche de l’autre : représentations du métissage et de l’altérité culturelle dans la création de Marguerite Duras - Ledwina, Anna (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
This paper analyses cultural diversity in Marguerite Duras’s novel L’Amant. Indochinese culture, as distinct from European culture, is particularly evident in the area of identity. The diversity of the constantly evolving identity confirms individual autonomy. — The novel reveals the writer’s obsession with becoming “someone else” by absorbing his history, language, and way of thinking and feeling until full identification with the other person. Personal understanding of multiculturalism allows Duras to show that cultural otherness awakes in the heroine an irresistible desire for transgression. — The above suggests that Duras’s work can be read as a confrontation with another person and realization of own and the other person’s otherness understood as a meeting of two different cultures.